Exploring demand reduction through design, durability and 'usership' of fashion clothes. (1st May 2017) - Fletcher, Kate
Abstract : Global planetary boundaries confer limits to production and consumption of material goods. They also confer an obligation to experiment, as individuals and collectively as society, with less-materially-intensive, but no less exuberant, ways of living. This paper takes up this mantle and explores materials demand reduction through a focus on design, fashion garments and the universal, everyday activity of wearing clothes. It takes as its starting point the design of longer-lasting products, a widely favoured strategy for increasing materials efficiency and reducing materials demand in many sectors, including fashion. Drawing on scholarship in the field of design for sustainability and ethnographic research conducted in 16 locations in nine countries about already-existing practices of intensive use and maintenance of clothing, this paper critiques the effectiveness of durability strategies to reduce the amount of materials used. It argues for an update in the familiar preference within sustainability debates for the 'techno-fix' to explore instead resourceful use of materials as emerging from human actions and relationships with material goods. It suggests that, while facilitated by design, technology and engineering, opportunities to reduce materials demand begin in individual and collective practices, which, in turn, have dynamic implications for use of materials. This article is part of the themed issue 'Material demand reduction'.